Asian regionalism versus global free trade: A simulation study on economic effects - Pekka Sulamaa; Mika Widgrén (The Research Institute of the Finnish Economy (ETLA), 2005)
This paper evaluates and compares the economic effects of global liberalization of world trade and regional integration scenario in which an Asian trading block is emerging. The evaluation is based on computable general equilibrium model GTAP (global trade analysis project) that has been widely used in analyses of big regime changes in world economy. The results show that global free trade is better for all regions in the investigation. Compared to the current trade regime, that does not hold since e.g. the new EU member states would be worse-off. The biggest winners of global free trade are Asian countries, Brazil and developing countries.
Keywords: F15; F17; 330; free trade; regionalism; GTAP model; Handelsregionalismus; Freihandel; International; Allgemeines Gleichgewicht; Asien